Enhancing Pre-Service Teachers’ Science Process Skills Through Open-Ended and Guided Inquiry-Based Learning - Jannah, Misbahul; Oviana, Wati; Hayati, Zikra; Hidayat, Riyan; Usman, Jarjani; Noris, M. (SCAD Independent, 2025)
This study investigates the effectiveness of open-ended and guided inquiry-based learning modules in enhancing Science Process Skills (SPS) among pre-service science teachers in Indonesia. The study responds to the limited research on SPS development under the implementation of the Independent Curriculum. A quasi-experimental non-equivalent pretest-posttest control group design was employed involving 204 pre-service teachers enrolled in Environmental Education courses, distributed across open-ended inquiry, guided inquiry, and conventional learning groups. Data were analyzed using two-way ANOVA and factorial MANOVA (3×2), considering gender and study program (Biology and Physics) as moderating variables. The results reveal statistically significant improvements in SPS for both inquiry-based groups compared to the conventional group (p < 0.001). Gender-based differences were also observed: female participants outperformed males in the guided inquiry group, while males performed better in the open-ended group. In addition, no significant differences were found between study programs. The findings underscore the potential of inquiry-based learning modules to foster key scientific competencies and suggest that gender-responsive strategies may further optimize SPS outcomes. This study contributes to international discussions on competency-based science teacher education and offers practical insights for curriculum design in national and global contexts.